A Note on Four-Dimensional Symmetry Algebras and Fourth-Order Ordinary Differential Equations. (4th February 2013) - Fatima, A.; Ayub, Muhammad; Mahomed, F. M.
Abstract : We provide a supplementation of the results on the canonical forms for scalar fourth-order ordinary differential equations (ODEs) which admit four-dimensional Lie algebras obtained recently. Together with these new canonical forms, a complete list of scalar fourth-order ODEs that admit four-dimensional Lie algebras is available.